PEMBERIAN MENGKUDU TERHADAPPENURUNAN HIPERTENSI PADA LANSIA DI WILAYAH KERJA PUSKESMAS TILANGO - Rona Febriyona; Inne Ariane Gobel (-, 2021)
Hypertension is a condition where there is an increase in blood pressure greater than 140/90 mm Hg, which is a degenerative disease of the elderly. Some nonpharmacologic therapy for treating hypertension one of them giving noni. The purpose of this study: to Know the Effect of Noni Against High Blood Pressure Drops On Elderly. The design of this study design quasy experimental design witte one-group pre-post test. The population in this study were 48 elderly and a sample a 20 respondents with sampling purposive sampling and using paired t-tests. The results showed that blood pressure before and after the intervention is very differen. with sig 0.000 (p <0.05) for the systole pressure, and diastolic blood pressure with sig 0.000 (p <0.05). There Kesimpulanya Noni Effect Of High Blood Pressure Decline In Elderly in Puskesmas Tilango.